Guided Of Project Based Learning On Seminar On ELT Subject At FKIP Universitas HKBP Nemmensen Pematangsiantar - Silalahi, Dumaris E.; Sinaga, Asima Rohana; Sihombing, Partohap S. R.; Silalahi, Josua (Universitas Wiralodra, 2024)
This research aims to investigate the use of Guided on Project based Learning on the seminar on ELT subject. This model focuses on the process of doing project through guiding by the lecturer. Guided of Project based Learning is applied into the seventh semester of EFL learners at FKIP Universitas HKBP Nommensen Pematangsiantar at acadmic year of 2023-2024. The data are taken from 84 learners. Quantitative research is done to investigate the effect of Guided of Project based Learning. The effect Guided is analysed based on the subjects’ project completely and respond based on questionnaires. This research finds the significant effect of Guided on Project based on Learning. It can be seen based on the mini research done the participants. They have maximal project based on lecturer guided. Guided on Project based Learning encourages and triggers the subjects to do the project systematically, Persistent. It means the guided of the lecturer on the Project based Learning has essential role to enhance not only the subjects’ cognitive but also their affective. Their projects are valuable to others through the national seminar. It indicates that the Guided on Project based Learning enables the subjects to be creative and innovative.